Electronic Structure and Bonding in Iron(II) and Iron(I) Complexes Bearing Bisphosphine Ligands of Relevance to Iron-Catalyzed C–C Cross-Coupling - Kneebone, Jared L. (Inorg Chem, 2015)
[Image: see text] Chelating phosphines are effective additives and supporting ligands for a wide array of iron-catalyzed cross-coupling reactions. While recent studies have begun to unravel the nature of the in situ-formed iron species in several of these reactions, including the identification of the active iron species, insight into the origin of the differential effectiveness of bisphosphine ligands in catalysis as a function of their backbone and peripheral steric structures remains elusive. Herein, we report a spectroscopic and computational investigation of well-defined FeCl(2)(bisphosphine) complexes (bisphosphine = SciOPP, dpbz, (tBu)dppe, or Xantphos) and known iron(I) variants to systematically discern the relative effects of bisphosphine backbone character and steric substitution on the overall electronic structure and bonding within their iron complexes across oxidation states implicated to be relevant in catalysis. Magnetic circular dichroism (MCD) and density functional theory (DFT) studies demonstrate that common o-phenylene and saturated ethyl backbone motifs result in small but non-negligible perturbations to 10Dq(T(d)) and iron–bisphosphine bonding character at the iron(II) level within isostructural tetrahedra as well as in five-coordinate iron(I) complexes FeCl(dpbz)(2) and FeCl(dppe)(2). Notably, coordination of Xantphos to FeCl(2) results in a ligand field significantly reduced relative to those of its iron(II) partners, where a large bite angle and consequent reduced iron–phosphorus Mayer bond orders (MBOs) could play a role in fostering the unique ability of Xantphos to be an effective additive in Kumada and Suzuki–Miyaura alkyl–alkyl cross-couplings. Furthermore, it has been found that the peripheral steric bulk of the SciOPP ligand does little to perturb the electronic structure of FeCl(2)(SciOPP) relative to that of the analogous FeCl(2)(dpbz) complex, potentially suggesting that differences in the steric properties of these ligands might be more important in determining in situ iron speciation and reactivity.